2022
DOI: 10.48550/arxiv.2203.10577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Statistical Analysis for the Neutrinoless Double-Beta Decay Matrix element of 48Ca

Abstract: Neutrinoless double beta decay (0νββ) nuclear matrix elements (NME) are the object of many theoretical calculation methods, and are very important for analysis and guidance of a large number of experimental efforts. However, there are large discrepancies between the NME values provided by different methods. In this paper we propose a statistical analysis of the 48 Ca 0νββ NME using the interacting shell model, emphasizing the range of the NME probable values and its correlations with observables that can be ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…An initial study along these lines for the 0νββ decay of 48 Ca-48 Sc- 48 Ti system can be found in Ref. [159].…”
Section: Other Methodsmentioning
confidence: 99%
“…An initial study along these lines for the 0νββ decay of 48 Ca-48 Sc- 48 Ti system can be found in Ref. [159].…”
Section: Other Methodsmentioning
confidence: 99%
“…However, no consensus estimates exist yet for NME fiducial values and covariances, although relevant work is in progress toward this goal [1,30]. Part of the planned strategy involves benchmarking nuclear models for 0νββ decay against a variety of data, coming from related electroweak and strong interaction processes or from nuclear structure [31][32][33].…”
Section: B Combination Of Xe Ge Te Constraintsmentioning
confidence: 99%
“…However, various many-body methods currently predict matrix elements that differ by up to a factor of a few [3] and almost all calculations miss an important recently acknowledged two-nucleon operator [4][5][6]. Since both 2νββ and 0νββ decays share initial and final states, are sensitive to spin and isospin operators, and may have correlated matrix elements [7,8], tests of M 2ν could help to reduce the theoretical uncertainties of 0νββ nuclear matrix elements.…”
Section: Introductionmentioning
confidence: 99%